Acute and subchronic toxicity study of the water extract from the fruits of Piper chaba hunter in rats - Jaijoy K. (2014)
The water extract from the fruits of Piper chaba Hunter was evaluated for acute and subchronic toxicity in both male and female rats. For the study of acute toxicity, a single oral dose of 5,000 mg/kg body weight was administered in rats (five females, five males). The results showed no signs of toxicity such as general behavior change, mortality, or change in gross appearance of internal organs. Subchronic toxicity was studied by daily oral doses (ten females, ten males) of 300, 600 and 1,200 mg/kg body weight for consecutive 90 days. The satellite group was treated with the extract at the dose of 1,200 mg/kg/day for 90 days and kept for other 28 days after treatment. The results showed no abnormalities in treated groups as compared to the controls. Although significantly different, all of the values were within normal limits. Neither gross abnormalities nor histopathological changes were observed. The results suggest that P. chaba extract does not produce acute or subchronic toxicity in either female or male rats. Industrial relevance: Herbal medicines are popular and extensively used in the developing world. In many places, they offer a more wide available and more affordable alternative to pharmaceutical drugs and natural food supplements. The data of the acute and subchronic toxicity studies on medicinal plants or preparations derived from them should be obtained in order to increase the confidence in its safety to human, particularly for use in the development of pharmaceutical. © 2010-2011. IJARNP-HS Publications.